Job Characteristics, Family Support and Wellbeing: Testing an Expanded Version of the Karasek Model - Javed, Uzma (The journal of contemporary issues in business and government, 2021)
This study tested an expanded version of Karasek‟ s Job Demands-Control-Support (JDCS) model, incorporating managerial support and family support policies as explanatory variables. In the context of changing workforce demographics, it is proposed that the availability of family support in workplaces may be a crucial component of support for employees. The Workplace Employee Relations Survey 2004 (WERS2004) is used to investigate the associations between job characteristics, expanded support and well-being. It demonstrates independent cumulative effects for both the JDCS Model and the availability of family support on the well-being of employees. In particular, family support is an important resource for reducing displeasure among female employees and enhancing pleasure among male employees. The findings also indicate that anxiety mediates the impact of job demands and managerial support on pleasure.